PAST AS FUTURE: THE SOUTH AFRICAN WAR, DUTCH OBSERVERS AND MILITARY MEMORY - De Jong, Henk (Scientia Militaria - South African Journal of Military Studies, 2013)
In 1900, the Dutch Ministry of War sent four military observers to South Africa, in an attempt to come to terms with the latest developments in the military field. Once in South Africa, the promising young Dutch officers selected for the mission remained focused strongly on decisive battles Jominian style, which they considered relevant for future warfare in Europe. They almost completely ignored guerrilla warfighting. However, inspired by the Boer commandos, their analysis of the Anglo-Boer War also ended in pleas for a fundamentally new relationship between army and society in Holland, and a new Dutch militia army organisation (a volksleger), comparable to the Boers’ commandos. Fascinatingly, this ideal of a militia army had probably much more to do with the observers’ interpretation of the Dutch national past and the values they regarded characteristic of it, than with contemporary South Africa, since the earliest forms of the Dutch army were also believed to have been a volksleger. In this way, the military observers from the Netherlands converted the South African present into Dutch history to serve their country’s national future.